2019
DOI: 10.21831/cp.v38i1.22245
|View full text |Cite
|
Sign up to set email alerts
|

M E D I A: Designing a Model of Ifl Learning Materials for Foreign Workers

Abstract: Communication gap because of linguistic difference and unavailability of specific learning materials become a problem of foreign workers working in Indonesia. A specific research that develops IFL learning materials to overcome these problems is needed. This study aims to develop and improve the quality of available IFL materials. Methodology used here is Research and Development, combining quantitative-qualitative approaches. The result of this study is: 1) M E D I A as a new framework learning materials with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 17 publications
0
8
0
2
Order By: Relevance
“…As prospective Indonesian language assistants (BIPA teachers), the candidates are required to show their proficiency in Indonesian language through taking a proficiency test known as Uji Kemahiran Berbahasa Indonesia (UKBI) which is also used as a reference for teachers to evaluate their proficiency level (Nugraheni, 2015). For instance, in the case of Mediyawati, et. al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As prospective Indonesian language assistants (BIPA teachers), the candidates are required to show their proficiency in Indonesian language through taking a proficiency test known as Uji Kemahiran Berbahasa Indonesia (UKBI) which is also used as a reference for teachers to evaluate their proficiency level (Nugraheni, 2015). For instance, in the case of Mediyawati, et. al.…”
Section: Discussionmentioning
confidence: 99%
“…vacation, business, and other related activities (Sujana, 2012). Also, through the implementation of the ASEAN Economic Community (AEC), foreign countries, particularly neighbouring countries in the region are free to share goods, exchange services, invest capitals, and send experts to Indonesia (Saputro & Arikunto, 2018) and the AEC even brings valuable attractions for foreign workers to do their business in Indonesia (Mediyawati, Lustyantie, & Emzir, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Penggunaan pendekatan kualitatif dianggap mampu memberikan penjelasan secara detail dan terperinci (Creswell, 2015). Penelitian tindakan kelas dipilih dikarenakan peneliti dapat meninjau langsung suasana kelas tempat berlangsungnya penelitian (Mediyawati et al, 2019).…”
Section: Metodeunclassified
“…By 2017, the number of foreign workers in Indonesia reached approximately 85.957 workers who need to communicate in Indonesian, and, of course, they should have to attend BIPA programs. Moreover, some foreign company, such as garment-based factory Hansae Utama Indonesia Co., and shoes-based factory Beesco Co., located in Karawang, requires their employees to be able to speak Indonesia for business communication (Mediyawati, Lustyantie, & Emzir, 2019). Furthermore, Andayani (2016) revealed that foreigners have motivation to learn Indonesian since it can support the diplomacy and enhance the knowledge about Indonesia; at the same time, by learning Indonesia, it can also explore its unique culture.…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, Gusnawaty & Nurwati (2019) have developed a learning model of Bahasa Indonesia based on local intercultural politeness to improve the foreigners' communicative competencies. Then, by applying research and development design, Mediyawati et al, (2019) developed a mnemonic framework materials with humanistic approach to develop and improve the quality of IFL materials for foreign workers called MEDIA.…”
Section: Introductionmentioning
confidence: 99%